2015
DOI: 10.1016/j.neuint.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant peroxiredoxin 6 protein rescues toxicity due to oxidative stress and cellular hypoxia in vitro, and attenuates prion-related pathology in vivo

Abstract: Protein misfolding, mitochondrial dysfunction and oxidative stress are common pathomechanisms that underlie neurodegenerative diseases. In prion disease, central to these processes is the post-translational transformation of cellular prion protein (PrPc) to the aberrant conformationally altered isoform; PrPSc. This can trigger oxidative reactions and impair mitochondrial function by increasing levels of peroxynitrite, causing damage through formation of hydroxyl radicals or via nitration of tyrosine residues o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 86 publications
3
20
0
Order By: Relevance
“…Similar reactive behavior of PRDX6 is known from extra-CNS cell lineages where oxidative stress upregulates PRDX6 level and promotes its translocation from the cytosol to the cell membrane allowing access to peroxidized lipids as the metabolic substrate [43]. In our previous work, we experimentally proved that PRDX6 renders astrocytes resistant to oxidative damage [8]. Astrocytes cultured from Prdx6 overexpressing mice exhibit increased resistance to in vitro oxidative insult while astrocytes cultured from Prdx6 −/− mice, conversely show significantly reduced viability.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Similar reactive behavior of PRDX6 is known from extra-CNS cell lineages where oxidative stress upregulates PRDX6 level and promotes its translocation from the cytosol to the cell membrane allowing access to peroxidized lipids as the metabolic substrate [43]. In our previous work, we experimentally proved that PRDX6 renders astrocytes resistant to oxidative damage [8]. Astrocytes cultured from Prdx6 overexpressing mice exhibit increased resistance to in vitro oxidative insult while astrocytes cultured from Prdx6 −/− mice, conversely show significantly reduced viability.…”
Section: Discussionsupporting
confidence: 55%
“…Here, we provide novel evidence that astrocytes play an active role in countering Aβ deposition, and identify PRDX6 protein as a key element of this process. PRDX6 is expressed by astrocytes but no other type of CNS glial cells [8,9]. As a prerequisite for this study, we determined that two-fold change in Prdx6 expression level does not affect astrocyte-resting state or alter soluble Aβ levels in AD Tg mice prior to appearance of Aβ plaques.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports found that some antioxidant proteins were increased in yeast R. mucilaginosa RCL‐11 stressed by copper (Irazusta et al., ). Peroxiredoxin 6, a unique member of the ubiquitous peroxiredoxin family, was recruited to protect cells against oxidative stress via reduction of H 2 O 2 , hydroperoxides, and peroxynitrite, caused by heavy metal (Asuni, Guridi, Sanchez, & Sadowski, ). In this study, mitochondrial peroxiredoxin 6 (spot 2002 and 5109) were found significantly enhanced in yeast cells against the heavy metal stress.…”
Section: Discussionmentioning
confidence: 99%
“…In ME7-infected prion disease models, Prdx6 deficiency worsens prion-related neuropathology [115]. These defects are caused by Prdx6 deficiency in astrocytes because PRDX6 is predominantly expressed in astrocytes rather than neurons in the brain [115].…”
Section: Prion Diseasementioning
confidence: 99%